1998
DOI: 10.1346/ccmn.1998.0460408
|View full text |Cite
|
Sign up to set email alerts
|

Diagenetic Transformation of Magnesite Pebbles and Cobbles to Sepiolite (Meerschaum) in the Miocene Eskişehir Lacustrine Basin, Turkey

Abstract: Magnesite pebbles in Miocene lacustrine conglomerates in northwest Turkey have been partially to totally replaced by sepiolite. Only 5% of the magnesite pebbles have been converted to essentially pure sepiolite; the rest represent mixtures of magnesite and sepiolite. This process of sepiolitization is documented by X-ray diffraction (XRD), chemical, scanning electron microscopy (SEM) and BrunauerEmmett-Teller (BET) techniques. These techniques show that the sepiolitization proceeds from the rim towards the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
2
10
0
1
Order By: Relevance
“…The MER, TPO, and SAN sepiolites have a structural formula close to the theoretical, both for the tetrahedral and the octahedral content. The MER sample is the most 'perfect' sepiolite from these data, in good agreement with those published by Ece (1998) for sepiolite from the same locality. Twelve samples contain variable amounts of tetrahedral AI, with >7 atoms of Mg p.h.u.c.…”
Section: Discussionsupporting
confidence: 89%
“…The MER, TPO, and SAN sepiolites have a structural formula close to the theoretical, both for the tetrahedral and the octahedral content. The MER sample is the most 'perfect' sepiolite from these data, in good agreement with those published by Ece (1998) for sepiolite from the same locality. Twelve samples contain variable amounts of tetrahedral AI, with >7 atoms of Mg p.h.u.c.…”
Section: Discussionsupporting
confidence: 89%
“…It was a very poorly crystallized sepiolite with fairly broad and poorly resolved reflections and with the 110 reflection appearing at 12.3 Å . Sepiolites with fairly similar XRD patterns with higher d values of the 110 reflection were reported in later studies (Yeniyol & Ö ztunalı, 1985;Yeniyol, 1986Yeniyol, , 1993aEce & Ç oban, 1994;Yalçın & Bozkaya, 1995;Chahi et al, 1997;Ece, 1998). These works describe poorly-ordered sepiolite having broad 110 reflections with high d values, showing a convoluted single reflection in the 26À30º2y region and remaining reflections which are not well resolved, rather similar to the work of Brindley (1959).…”
Section: Discussionsupporting
confidence: 84%
“…If there were any transitional phase between these minerals, there would be a gradational contact between sepiolite-and loughlinite-dominated claystone. Moreover, SEM images also indicate that loughlinite developed as a network of fibers on the inner surfaces of dissolution voids in domains of volcanic glass, in contrast to sepiolite, which occurs as bridging fibers between crystallites of dolomite, indicating that these minerals are formed authigenically under different physicochemical environmental conditions rather than resulting from a transformation process from one to the other (Galán & Castillo 1984, Jones 1986, Jones & Galán 1988, Ece & Çoban 1994, Ece 1998, Singer et al 1998. On the other hand, Wollast et al (1968) observed the precipitation of sepiolite under laboratory condi-tions, but they did not explain the precipitation of loughlinite.…”
Section: Discussionmentioning
confidence: 99%